STUDY ON IN VITRO PROPAGATION AND CULTIVATION OF ANOECTOCHILUS LYLEI ROLFE EX DOWNIES AT EX VITRO CONDITION - Phan Xuân Huyên; Nguyễn Văn Kết; Phan Hoàng Đại; Nguyễn Thị Cúc (Tạp chí Khoa học Đại học Đà Lạt)
In the present study, we investigated in vitro propagation and cultivated Anoectochilus lylei Rolfe ex Downies at ex vitro condition, which is one of the valuable herbal plants and has been proved to be good for human health. The results showed that, MS medium supplemented with 1 mg/l BA gave the best on in vitro shoot regeneration after 60 days of culture, with 5.70 shoots/explant, shoot height of 3.72 cm. MS medium containing 0 – 2 mg/l NAA was found to be the most suitable for in vitro root regeneration after 30 days of culture, root regeneration rate of 100%. Substrate of 90% coconut fiber powder combination with 10% rice husk was the best substrate for acclimatization of the plantlet after 60 days of cultivation, with plant height of 7.00 cm, root length of 4.74 cm, survival rate of 100%. For the cultivation of Anoectochilus lylei, after 120 days of cultivation, the result showed that, the plants which were used with Nitrophoska® Foliar of 2 g/l (plant height of 11.00 cm, root length of 7.60 cm, fresh weight of 1.81 g/plant, survival rate of 100%) were better than Nitrophoska® Foliar of 1 g/l (plant height of 9.80 cm, root length of 6.70 cm, fresh weight of 1.64 g/plant, survival rate of 100%).